Antibiotic resistance patterns of environmental bacteria from sewage water in Vellore, India: isolation, virulence analysis, and characterization - Barnwal, Surbhi Kumari; Saleh, Arabi Mohammed (Frontiers in Microbiology, 2025)
Globally, the rise of antibiotic resistance is a pressing One Health concern, where environmental sources, particularly wastewater, play a critical role in the dissemination of resistant bacteria. The influx of pharmaceutical waste, likely to contain antibiotics, into the environment would lead to the chronic presence of antibiotics and development of resistance in environmental bacteria. This study aimed to investigate the prevalence and antibiotic resistance patterns of bacterial isolates obtained from sewage receiving hospital wastewater. Sewage samples were collected from four different locations in Vellore, Tamil Nadu, India. The samples were further analyzed using LC/MS for quantification of amoxicillin, meropenem, and vancomycin. The bacterial isolates were obtained by both direct and enrichment culture techniques. The isolates were phenotypically characterized by analyzing the colony morphology and through gram staining, and virulence tests (hemolysis assay, biofilm formation assay, and protease, amylase and lipase activity assays). Minimum inhibitory concentrations (MICs) against amoxicillin, meropenem, and vancomycin were determined using both antibiotic gradient strips and broth microdilution methods, following EUCAST guidelines. Molecular identification was performed using 16S rRNA gene sequencing. Although antibiotics were below the limit of quantification (BLQ) in the samples, significant resistance was observed among the isolates. A total of 10 bacterial strains, including Stenotrophomonas, Sphingobium, Brucella, Agrobacterium, Ochrobactrum, Acinetobacter, Klebsiella, and Pandoraea were identified. Most of the isolates exhibited multidrug resistance (MDR), with notable variability in MIC values (p < 0.05). Pandoraea sp. strain VITSA19 displayed the highest resistance to all the tested antibiotics (≥4,096 μg/mL for amoxicillin, ≥512 μg/mL for meropenem and ≥4,096 μg/mL for vancomycin). Two isolates, Stenotrophomonas sp. strain VITSA1 and Stenotrophomonas pavanii strain VITSA2, demonstrated hemolysin and protease production. These findings underscore sewage as a reservoir of MDR bacteria and highlight the environmental dimension of antibiotic resistance spread. From a One Health perspective, the study emphasizes the urgent need for integrated environmental antimicrobial resistance (AMR) surveillance and improved wastewater treatment practices to mitigate the risk of resistance transmission to human and ecological health.